(untitled) (Eurasian Scientific Herald, 2023)
Clothing design uses a combination of fashionable silhouette of clothes, elements of traditional culture and relevant materials. In this process, it is necessary to use the model of national and international fashion design. In order to create a harmonious connection between the civilization of the Eastern and Western worlds, it is necessary to preserve the cultural vitality of traditional clothing and to combine it with modern design concepts. The relevance of the research topic is characterized by the need to develop a comprehensive approach to solving design problems. The purpose of the work is to systematize the means of creating modern clothes based on the results of a comparative analysis of the methods of creating a national dress form. The results of the comparative analysis showed that modern clothes actively use the constructive means of forming traditional clothes: the minimum number of articulations, through design lines and special forming means. As a result of the study, the correctness of the structural parts was determined, which allows to simplify the design process. The identified trend is related to the universality of clothing in modern fashion, the current state of elimination of gender and national differences